Unusual Origin of Type 1 Atrioventricular Block with Comments on Wenckebach's Contribution - Tandon, Anumeha; Simpson, Leo; Assar, Manish D. (Proceedings - Baylor University. Medical Center, 2011)
We present a case that demonstrates the rare occurrence of type 1 second-degree atrioventricular block (Wenckebach or Mobitz type 1 block) as a result of block in the infranodal conduction system. This extremely rare occurrence often predicts progression to complete heart block and necessitates cardiac pacing. It also demonstrates the value of an electrophysiological study and exercise stress testing to identify the level of block, predict prognosis, and plan a management strategy.